2022
DOI: 10.4103/ijo.ijo_234_22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and correlation of corneal endothelium parameters with the severity of primary glaucoma

Abstract: Purpose: To evaluate and correlate corneal endothelium parameters with the severity of primary glaucoma. Methods: This prospective case-control study was conducted on 150 eyes of 80 newly diagnosed primary open-angle glaucoma (POAG), chronic primary angle-closure glaucoma (cPACG), and normal-tension glaucoma (NTG) patients in a tertiary care center. Endothelial parameters including endothelial cell count (ECC), percentage of hexagonal cells, and coefficient of variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
1
Order By: Relevance
“…As stated previously, hyperopia is a significant PACG risk factor, and several studies have found lower CD in PACG compared to open-angle glaucoma [ 38 ] or compared to healthy controls [ 35 ]. Both in emmetropes and in hyperopes we have found a correlation between CD, CV and ACD—a shallower anterior chamber is correlated with a decrease in endothelial cell density and increase in variability, which may have important repercussions over the patient’s lifetime.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As stated previously, hyperopia is a significant PACG risk factor, and several studies have found lower CD in PACG compared to open-angle glaucoma [ 38 ] or compared to healthy controls [ 35 ]. Both in emmetropes and in hyperopes we have found a correlation between CD, CV and ACD—a shallower anterior chamber is correlated with a decrease in endothelial cell density and increase in variability, which may have important repercussions over the patient’s lifetime.…”
Section: Discussionmentioning
confidence: 97%
“…The corneal endothelium is the innermost layer of the cornea, consisting of tightly interconnected cells, with an essential role in maintaining proper corneal hydration and transparency [ 34 ]. It is a single-cell layer, with limited capacity for regeneration [ 35 ]. In normal eyes, the annual rate of cell loss is 0.6%, and there are several systemic and ocular conditions which may increase this rate during the course of the patient’s life [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, в 2022 году D. Kang и соавт. [38] опубликовали результаты исследования о взаимосвязи параметров эндотелия роговицы с тяжестью первичной глаукомы. Количество эндотелиальных клеток роговицы снижалось с увеличением тяжести, поскольку у пациентов с ранней глаукомой плотность эндотелиальных клеток составляла 2284 кл./мм 2 , при умеренной -2261 кл./мм 2 , при тяжёлой -2086 кл./мм 2 , и разница была статистически значимой.…”
Section: глаукома как мультифакториальное нейродегенеративное заболев...unclassified